Cabs With Powered Height Adjustment (Rail Mounted) - Objective (The National Institute for Occupational Safety and Health (NIOSH), 1978)
Provide optimum visibility of mining operations while maintaining protection and comfort for ma-chine operators. Approach Cabs and canopies with hydraulically powered variable-height control were developed for several machines and tested in underground mining operations. How It Works From his position in the cab, the operator can raise or lower the cab, selecting a height that offers either more visibility of the working place or greater clearance for tramming. The entire cab enclosure moves up and down on guide rollers that ride on a pair of rails, and is actuated by a hydraulic cylinder controlled from within the cab. Normal working heights, for each of the four different cabs developed, are with the cab bottom from 6 to 8 inches above the mine bottom. A typical range of elevation (excursion) afforded by this design is shown in Figure 1.